Small EUS-suspected gastrointestinal stromal tumors of the stomach: An overview for the current state of management - DUMAN, DENİZ (MEDKNOW PUBLICATIONS & MEDIA PVT LTD, 2016)
Gastrointestinal stromal tumors (GIST) are the most common mesenchymal tumors found in the gastrointestinal (GI) tract, with the stomach being the most common site. They represent a distinct group of GI tumors originating from the interstitial cells of Cajal and are characterized by gain-of-function mutations of KIT. KIT oncoprotein serves as both diagnostic and therapeutic targets. Prognosis is related to size, mitotic activity, and site of the tumor. Asymptomatic, small endoscopic ultrasonography (EUS)-suspected GISTs are increasingly encountered with the wide availability of endoscopic/endosonographic examination. The majority of small GISTs are biologically indolent, albeit possibly harboring c-KIT gene mutations. An ongoing controversy exists regarding the management and surveillance policy for small gastric GISTs. A number of reports on the management of GISTs have been published, not confidently addressing the issue of gastric GISTs of small size. This work provides an overview on the current state of management considerations, specifically focusing on small EUS-suspected gastric GISTs, which are increasingly encountered by clinicians.
Keywords: Gastrointestinal stromal tumor (GIST); small hypoechoic muscularis propria (MP) lesion; surgery; surveillance; FINE-NEEDLE-ASPIRATION; GASTRIC SUBEPITHELIAL TUMORS; MUSCULARIS PROPRIA LAYER; ENDOSCOPIC SUBMUCOSAL DISSECTION; CLINICAL-PRACTICE GUIDELINES; OF-FUNCTION MUTATIONS; CELL TUMORS; FOLLOW-UP; ULTRASOUND ELASTOGRAPHY; DIFFERENTIAL-DIAGNOSIS